ANALISIS KOMPARASI KINERJA FINANSIAL PETANI MITRA DAN NON MITRA PADA USAHATANI TEMBAKAU VIRGINIA DI KABUPATEN LOMBOK TIMUR OF INDONESIA - Addinul Yakin; Rizqi Auliya’u Rahmatin (JURNAL AGRIMANSION, 2023)
Tobacco is a strategic commodity with significant economic value and profitable cultivation for farmers. Establishing a business partnership is a viable approach for achieving this goal. The purpose of this study was to compare the financial performance of partner and non-partner farmers in East Lombok district tobacco cultivation. Profit, return on capital, net profit margin (NPM), and profitability are used to evaluate financial performance. All of the foregoing measures demonstrated that the financial performance of Virginia tobacco farmers who participated in the partnership program was significantly higher than that of farmers who did not participate. This is achievable due to the fact that farmer partnerships make it possible to gain knowledge and direction on optimal tobacco farming (good practices), so allowing farmers to increase their production and productivity. In addition, partner farmers have pricing certainty, allowing them to generate more earnings. As a result, tobacco growers and farmers of other commodities are encouraged to form mutually advantageous relationships with related businesses in order to increase their profitability